2016
DOI: 10.4103/0973-1482.147716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immunophenotypic aberrancies in adult and childhood acute lymphoblastic leukemia: A study from Northern India

Abstract: In summary, CD117 is a relatively frequently expressed myeloid marker contrary to earlier reports which describes its rare expression. Pediatric and adult ALL cases with low blast count and CD34 positivity are more likely to express aberrant myeloid markers. Current study also supports that myeloid antigen expression in both adult and pediatric ALL is not associated with adverse presenting clinical and biological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
7
20
0
1
Order By: Relevance
“…HLA-DR frequency in B-ALL was (91.6%) and for T-ALL was (12.5%). These results matched with Sharma et al, who found that CD34 expression in ALL were seen in 67.3% of all ALL cases and the expression was more frequent in B-ALL (70.3%) as compared to T-ALL (51%) [16]. Another Indian study found that CD34 positivity was much higher in B-lineage ALL (82%) than in T-ALL (35%), (p < 0.0001) [17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…HLA-DR frequency in B-ALL was (91.6%) and for T-ALL was (12.5%). These results matched with Sharma et al, who found that CD34 expression in ALL were seen in 67.3% of all ALL cases and the expression was more frequent in B-ALL (70.3%) as compared to T-ALL (51%) [16]. Another Indian study found that CD34 positivity was much higher in B-lineage ALL (82%) than in T-ALL (35%), (p < 0.0001) [17].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the aberrancy percentage was 45.8% of all leukemic patients, was found in 66 patients, lymphoid antigen markers expression in AML was in 40 patients (45.5%), and aberrancy incidence of myeloid antigen expression on ALL was in 26 patients (46.4%). Some studies showed comparable results, in which aberrant myeloid antigen expression was seen in 42.5% of ALL cases and 47% of AML cases showed aberrant lymphoid antigen expression [16] [20]. On the other hand many studies showed lower frequency of aberrant immunophenotyping [7] [21].…”
Section: Discussionmentioning
confidence: 98%
“…Contudo, a expressão do antígeno mielóide é maior em casos de LLA em adultos do que em crianças. (Sharma et al, 2016) A adição dos marcadores CD135 e CD117 ao diagnóstico pode prever aberrações moleculares em configurações de T-ALL em crianças, principalmente segregando pacientes com FLT3-ITD, que se beneficiariam do tratamento com inibidores de tirosina. (Noronha et al, 2016) Para Ren et al (2019) a combinação dos anticorpos CD9, CD11b e HLA-DR apresenta alta sensibilidade e especificidade e pode ser utilizada para diagnosticar APL.…”
Section: Discussõesunclassified
“…5 on neoplastic cells different from the process of normal hematopoietic maturation. 7 In ALL, these aberrancies include: a) Expression of myeloid antigens in ALL, B-lineage antigens in T-ALL or T-lineage antigens in B-ALL, b) co-expression of early (immaturity associated) antigens with mature ones c) antigen over expression or under expression or absence of expression. 7 The expression of aberrant myeloid antigen (MyAg) has varied between 5 and 86% in various studies.…”
Section: Introductionmentioning
confidence: 99%
“…7 In ALL, these aberrancies include: a) Expression of myeloid antigens in ALL, B-lineage antigens in T-ALL or T-lineage antigens in B-ALL, b) co-expression of early (immaturity associated) antigens with mature ones c) antigen over expression or under expression or absence of expression. 7 The expression of aberrant myeloid antigen (MyAg) has varied between 5 and 86% in various studies. 7 The expression of two or more lineage specific antigens poses a dilemma in assigning leukemia to any one lineage.…”
Section: Introductionmentioning
confidence: 99%